LO73: The state of the evidence for emergency medical services care of adult patients with sepsis: an analysis of appraised research from the Prehospital Evidence-Based Practice (PEP) program. (May 2019) - Greene, J.; Carter, A.; Goldstein, J.; Jensen, J.; Swain, J.; Brown, R.; Leroux, Y.; Lane, D.; Simpson, M.
Abstract : Introduction : The Prehospital Evidence-Based Practice (PEP) program is an online, freely accessible, continuously updated Emergency Medical Services (EMS) evidence repository. This summary describes the research evidence for the identification and management of adult patients suffering from sepsis syndrome or septic shock.Methods : PubMed was searched in a systematic manner. One author reviewed titles and abstracts for relevance and two authors appraised each study selected for inclusion. Primary outcomes were extracted. Studies were scored by trained appraisers on a three-point Level of Evidence (LOE) scale (based on study design and quality) and a three-point Direction of Evidence (DOE) scale (supportive, neutral, or opposing findings based on the studies' primary outcome for each intervention). LOE and DOE of each intervention were plotted on an evidence matrix (DOE x LOE).Results : Eighty-eight studies were included for 15 interventions listed in PEP. The interventions with the most evidence were related to identification tools (ID) (n = 26, 30%) and early goal directed therapy (EGDT) (n = 21, 24%). ID tools included Systematic Inflammatory Response Syndrome (SIRS), quick Sequential Organ Failure Assessment (qSOFA) and other unique measures. The most common primary outcomes were related to diagnosis (n = 30, 34%), mortality (n = 40, 45%) and treatment goals (e.g. time to antibiotic) (n = 14, 16%). The evidence rank for the supported interventions were: supportive-high quality (n = 1, 7%) for crystalloid infusion, supportive-moderate quality (n = 7, 47%) for identification tools, prenotification, point of care lactate, titrated oxygen, temperature monitoring, and supportive-low quality (n = 1, 7%) for vasopressors. The benefit of prehospital antibiotics and EGDT remain inconclusive with a neutral DOE. There is moderate level evidence opposing use of high flow oxygen.Conclusion : EMS sepsis interventions are informed primarily by moderate quality supportive evidence. Several standard treatments are well supported by moderate to high quality evidence, as are identification tools. However, some standard in-hospital therapies are not supported by evidence in the prehospital setting, such as antibiotics, and EGDT. Based on primary outcomes, no identification tool appears superior. This evidence analysis can guide selection of appropriate prehospital therapies.